An investigation into “two hit” effects of BDNF deficiency and young-adult cannabinoid receptor stimulation on prepulse inhibition regulation and memory in mice - Klug, Maren; Van Den Buuse, Maarten (Frontiers in Behavioral Neuroscience, 2013)
Reduced brain-derived neurotrophic factor (BDNF) signalling has been shown in the frontal cortex and hippocampus in schizophrenia. The aim of the present study was to investigate whether a BDNF deficit would modulate effects of chronic cannabis intake, a well-described risk factor for schizophrenia development. BDNF heterozygous mice (HET) and wild-type controls were chronically treated during weeks 6, 7 and 8 of life with the cannabinoid CB1 receptor agonist, CP55,940 (CP). After a 2-week delay, there were no CP-induced deficits in any of the groups in short-term spatial memory in a Y-maze task or novel object recognition memory. Baseline prepulse inhibition (PPI) was lower but average startle was increased in BDNF HET compared to wild-type controls. Acute CP administration before the PPI session caused a marked increase in PPI in male HET mice pre-treated with CP but not in any of the other male groups. In females, there were small increases of PPI in all groups upon acute CP administration. Acute CP administration furthermore reduced startle and this effect was greater in HET mice irrespective of chronic CP pre-treatment. Analysis of the levels of [3H]CP55,940 binding by autoradiography revealed a significant increase in the nucleus accumbens of male BDNF HET mice previously treated with CP but not in any of the other groups or in the caudate nucleus. These results show that BDNF deficiency and chronic young-adult cannabinoid receptor stimulation do not interact in this model on learning and memory later in life. In contrast, male ‘two hit’ mice, but not females, were hypersensitive to the effect of acute CP on sensorimotor gating. These effects may be related to a selective increase of [3H]CP55,940 binding in the nucleus accumbens, reflecting up-regulation of CB1 receptor density in this region. These data could be of relevance to our understanding of differential ‘two hit’ neurodevelopmental mechanisms in schizophrenia.